Factors Influencing Neonatal Health Conditions in Zambia: A Systematic Literature Review (British Journal of Multidisciplinary and Advanced Studies, 2024)
Neonatal mortalities and health outcomes among infants are serious health conditions facing public health practice in Zambia and hindering the attainment of SDG 3 and target 3.2 by 2030. To address the problem of neonatal mortalities and health conditions in Zambia and inform relevant intervention, the present systematic literature review aimed to investigate the factors influencing neonatal mortalities and health conditions in Zambia. Methodology: A systematic literature review was done in order to assess factors influencing neonatal disorders in Zambia to document findings other researchers in Zambia had reported. The search strategies involved reviewing literature from Zambia using Google scholar and PubMed data bases. Selection of studies considered as eligible by this systematic literature review tool three steps namely topics only, abstracts and full articles. A CASP systematic review checklist 2018 tool was used to appraise included studies validity, results and relevance of results to the local situation. Findings of the articles selected for inclusion on the study were analyzed thematically based on themes generated from the study objective and presented in a narrative form. A data extraction table utilized and included among others a critical appraisal section for the included studies. Findings: On the prevalence of neonatal mortalities and health conditions among newborns in Zambia, the present systematic literature review found that in Zambia, neonatal mortalities and health disorders are a very serious public health problem among new borns in the nation and that majority of Zambian neonates die in a span of seven days after birth in with the rural regions which are underdeveloped bearing the brunt of these neonatal deaths and health conditions. The health conditions among Zambian neonates include respiratory syncytial virus, sepsis, premature births and respiratory dysfunctions among others. Regarding the factors influencing neonatal disorders among newborns in Zambia, the review found that in Zambia, neonatal mortalities and health conditions are caused by several factors namely neonatal sepsis, intrauterine infections, birth asphyxia, bacterial infections, premature deliveries and low-birth weight as the main factors while others include but are not limited to maternal level of education, being a male infant, severe intrapartum incidents respiratory syncytial virus, twin pregnancies and placental abruption. The study therefore concludes that neonatal mortalities and disorders are very prevalent among Zambian newborns with neonatal sepsis and low birth weight being some of the key causes of these health outcomes.